PENERAPAN MODEL KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 005 BATU GAJAH KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Amrina, Amrina; Daud, Damanhuri; Alim, Jesi Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : This research is conducted by the low students’ achievement in Science lesson, with the average class score is 55,87. Whereas minimum criteria passing grade the Science is 75.with the number of the student is 23 and only 6 students from them (26%) reach KKM with the classical completeness 26,06%. This research is the Classroom Action Research. The Research Goal is to increase the study achievement in Science lesson by five grade students of Public Elementary School 005 Batu Gajah Pasir Penyu Sub district Indragiri Hulu Regency. This research was conducted in 6th March until 27 March 2015 with two phases. The Subject of this research is the students of Public Elementary School 005 Batu Gajah with 23 students become a data sources. The instrument collecting data in this thesis is Syllabus, Lesson Plan and students Worksheet. This thesis showed the students achievement which is gained from the daily examination before action with average score is 55,87 and increase in first phase with average 78,61 and second phase become 84,70. Teacher activities in teaching learning process in first phase is 50%and at the second phase is 76,19%. In second Phase in the first meeting 91,30% and second meeting becomes 95.83%. The result of the research in class Vb of Public Elementary School 005 Batu Gajah gave evidence that the Implementation of Cooperative Learning Model can increase the students’ achievement of Science lesson in five grade students of Public Elementary School 005 Batu Gajah.Keywords : The Implementation of Corporative Model in Science Achievement.